Photoelectrochemical CO2 Reduction by a Molecular Cobalt(II) Catalyst on Planar and Nanostructured Si Surfaces. Issue 37 (4th August 2016) - He, Da; Jin, Tong; Li, Wei; Pantovich, Sebastian; Wang, Dunwei; Li, Gonghu
Abstract: In the presence of a molecular Co II catalyst, CO2 reduction occurred at much less negative potentials on Si photoelectrodes than on an Au electrode. The addition of 1 % H2 O significantly improved the performance of the Co II catalyst. Photovoltages of 580 and 320 mV were obtained on Si nanowires and a planar Si photoelectrode, respectively. This difference likely originated from the fact that the multifaceted Si nanowires are better in light harvesting and charge transfer than the planar Si surface. Abstract : Bring to light : Photoelectrochemical CO2 reduction was achieved by coupling a molecular Co II catalyst with Si photoelectrodes. The presence of a small amount of water significantly improved the performance of the Co II catalyst. A much greater photovoltage was obtained on Si nanowires than on a planar Si photoelectrode due to the multifaceted feature and better light harvesting of Si nanowires.